Performance evaluation of PAPR reduction with SER and BER by modified clipping & filtering in 3GPP LTE downlink - Arafat, M. Y. Arafat; Abd Latif, Suhaimi; Alam, M. K.; Haque, S. S.; Akte, M. (IJCSSE, 2014)
This paper work focuses on performance analysis of PAPR reduction of orthogonal frequency division multiplexing (OFDM) using amplitude clipping & filtering based design. Now a days one of the most proficient multi-carrier transmission techniques widely used today is orthogonal frequency division multiplexing (OFDM) which has been implemented by the next generation wireless communication technology: Long Term Evolution (LTE). Extra robustness to multipath fading and impulse noise is provided OFDM. It eliminates inter symbol interference (ISI) & inter carrier interference (ICI) with certain procedure. Therefore peak to average power ratio (PAPR) is the basic problem with OFDM. However in this paper we proposed a reduction procedure of the PAPR by using clipping and filtering. Here we use a composed high pass , low pass & Chevyshev band pass filter II after amplitude clipping to reduce the PAPR. The performance of the system in terms of bit error rate (BER) and symbol error rate (SER) is also investigated as a new filter based clipping method is proposed. Our proposed clipping method with and composed high pass the Chevyshev bandpass filter II in PAPR performance of the system with a little compromise of BER & SER showing the significant improvement in Quadrature Amplitude Modulation (QAM).